Characterization of lncRNA/circRNA-miRNA-mRNA network to reveal potential functional ceRNAs in the skeletal muscle of chicken - Pan, Zegun; Yang, Chaowu; Zhao, Ruipeng; Jiang, Xiaosong; Yu, Chunli; Li, Zhixiong (Frontiers in Physiology, 2022)
Skeletal muscle, comprising approximately 40% of body mass, is a highly complex and heterogeneous tissue serving a multitude of functions in the organism. Non-coding RNAs (ncRNAs) are known to participate in skeletal muscle development as critical regulators. However, the regulatory mechanisms of ncRNAs on chicken muscle traits are not well understood. In the present study, we collected the leg muscle from male embryos of Tibetan chicken at embryonic (E) 10 and E18 for RNA sequencing. A total of 6,583 differentially expressed mRNAs (DEMs) including 3,055 down-regulated and 3,528 up-regulated were identified in E18. We identified 695 differentially expressed lncRNAs (DELs) (187 down-regulated and 508 up-regulated) and 1,906 differentially expressed circRNAs (DECs) (1,224 down-regulated and 682 up-regulated) in E18. Among the 130 differentially expressed miRNAs (DEMIs), 59 were up-regulated and 71 were down-regulated in E18. Numerous DEMs and target genes for miRNAs/lncRNAs were significantly enriched in the muscle system process and cell cycle. We constructed a miRNA-gene-pathway network by considering target relationships between genes related to skeletal muscle development and miRNAs. A competing endogenous RNA (ceRNA) network was also constructed by integrating competing relationships between DEMs, DELs, and DECs. Several DELs and DECs were predicted to regulate the ADRA1B, ATP2A2, ATP2B1, CACNA1S, CACNB4, MYLK2, and ROCK2 genes. We discovered the crosstalk between the ncRNAs and their competing mRNAs, which provides insights into ceRNA function and mechanisms in the skeletal muscle development of chicken.